Evaluation of the MIM Symphony treatment planning system for low‐dose‐rate‐ prostate brachytherapy - Dhanesar, Sandeep K. (J Appl Clin Med Phys, 2015)
MIM Symphony is a recently introduced low‐dose‐rate prostate brachytherapy treatment planning system (TPS). We evaluated the dosimetric and planning accuracy of this new TPS compared to the universally used VariSeed TPS. For dosimetric evaluation of the MIM Symphony version 5.4 TPS, we compared dose calculations from the MIM Symphony TPS with the formalism recommended by the American Association of Physicists in Medicine Task Group 43 report (TG‐43) and those generated by the VariSeed version 8.0 TPS for iodine‐125 (I‐125; Models 6711 and IAI‐125A), palladium‐103 (Pd‐103; Model 200), and cesium‐131 (Cs‐131; Model Cs‐1). Validation was performed for both line source and point source approximations. As part of the treatment planning validation, first a QA phantom (CIRS Brachytherapy QA Phantom Model 045 SN#D7210‐3) containing three ellipsoid objects with certified volumes was scanned in order to check the volume accuracy of the contoured structures in MIM Symphony. Then the DICOM data containing 100 patient plans from the VariSeed TPS were imported into the MIM Symphony TPS. The 100 plans included 25 each of I‐125 pre‐implant plans, Pd‐103 pre‐implant plans, I‐125 Day 30 plans (i.e., from 1 month after implantation), and Pd‐103 Day 30 plans. The dosimetric parameters (including prostate volume, prostate D90 values, and rectum V100 values) of the 100 plans were calculated independently on the two TPSs. Other TPS tests that were done included verification of source input and geometrical accuracy, data transfer between different planning systems, text printout, 2D dose plots, DVH printout, and template grid accuracy. According to the line source formalism, the dosimetric results between the MIM Symphony TPS and TG‐43 were within 0.5% (0.02 Gy) for [Formula: see text]. In the line source approximation validation, MIM Symphony TPS values agreed with VariSeed TPS values to within 0.5% (0.09 Gy) for [Formula: see text]. Similarly, in point source approximation validation, the MIM Symphony values agreed to within 1% of the TG‐43 and VariSeed values for [Formula: see text]. The volume calculations obtained from the MIM Symphony TPS for the CIRS Brachytherapy QA Phantom were within 1% of the actual volume of the phantom. For the clinical cases, the volume and dosimetric parameter calculations for the prostate and rectum did not differ substantially between the pre‐implant and Day 30 plans. Overall, our investigations showed negligible differences in dosimetry calculations and planning parameters between the two TPSs. The tests done to check the performance of the MIM Symphony TPS, such as the library data, data transfer, isodose and DVH printout, were found to be satisfactory. On the basis of these results, we conclude that the MIM Symphony TPS can be used as an alternative to the VariSeed TPS for low‐dose‐rate prostate brachytherapy. PACS numbers: 87.53.Jw; 87.55.D‐, 87.55.Qr